Recycle Concrete Waste from Laboratory as Aggregates for Concrete - Darasahudin, Dalila Sarah (Universiti Teknologi PETRONAS, 2017)
Concrete block from laboratory can be recycled to lessen the cost of transportation to transport the waste to the landfill and also diminish the absolute of concrete wastes. Improving and recycle the crushed concrete block as coarse aggregate would lead to economic profits. This experiment study aimed to use crushed concrete block from the concrete laboratory as recycled coarse aggregate in concrete mixture. The controlled concrete mixture will be correlated with concrete mixture added with some amount of recycled aggregates as replacement with normal coarse aggregates. The experimental was conducted to compare the strength of normal coarse aggregates and recycled coarse aggregates that have been added in concrete mixture to study the hypothetical use of recycled coarse aggregates in constructions. Before conducting the experiment, the concrete block waste will be crushed to coarse aggregate size and sieving process will be carried out to get the desired size to produce new concrete block. Finally, compressive strength and tensile strength tests will be evaluated. The result of the tests will be altered based on the different ratio of recycled coarse aggregate replacement in the concrete mixture.